Immune Reactivation by Cell-Free Fetal DNA in Healthy Pregnancies Re-Purposed to Target Tumors: Novel Checkpoint Inhibition in Cancer Therapeutics - Enninga, Elizabeth Ann L.; Nevala, Wendy K.; Holtan, Shernan G.; Markovic, Svetomir N. (Frontiers in Immunology, 2015)
The role of the immune system in cancer progression has become increasingly evident over the past decade. Chronic inflammation in the promotion of tumorigenesis is well established, and cancer-associated tolerance/immune evasion has long been appreciated. Recent developments of immunotherapies targeting cancer-associated inflammation and immune tolerance such as cancer vaccines, cell therapies, neutralizing antibodies, and immune checkpoint inhibitors, have shown promising clinical results. However, despite significant therapeutic advances, most patients diagnosed with metastatic cancer still succumb to their malignancy. Treatments are often toxic, and the financial burden of novel therapies is significant. Thus, new methods for utilizing similar biological systems to compare complex biological processes can give us new hypotheses for combating cancer. One such approach is comparing trophoblastic growth and regulation to tumor invasion and immune escape. Novel concepts regarding immune activation in pregnancy, especially reactivation of the immune system at labor through toll like receptor engagement by fetal derived DNA, may be applicable to cancer immunotherapy. This review summarizes mechanisms of inflammation in cancer, current immunotherapies used in the clinic, and suggestions for looking beyond oncology for novel methods to reverse cancer-associated tolerance and immunologic exhaustion utilizing mechanisms encountered in normal human pregnancy.